Effectiveness Of Microhydro Power Plant Teaching Aid To Improve The Science Process Skills Of Physics Education Students at UIN Sayyid Ali Rahmatullah Tulungagung - Desyana Olenka Margaretta; Kurniawan, Husni Cahyadi; Paramarta, Fatwa; Resbiantoro, Gaguk (Journal of Education and Learning Sciences, 2025)
Physics learning in the Electricity and Magnetism course requires strong science process skills; however, abstract instruction with limited laboratory activities often results in low SPS achievement. This study aimed to examine the effectiveness of a Microhydro Power Plant (MHPP) teaching aid in improving students’ science process skills. A quasi-experimental method with a nonequivalent control group design was employed. The participants consisted of 20 students in the experimental group and 19 students in the control group. Data were collected through SPS pretests and posttests and analyzed using N-gain and an independent samples t-test. The results showed that the experimental group’s SPS scores increased from a range of 6–23 to 24–32, with N-gain values ranging from 0.57 to 0.93 (moderate to high category). In contrast, the control group obtained N-gain values between 0.07 and 0.43 (low to moderate category). The t-test results indicated a significant difference between the two groups (p = 0.001 < 0.05). These findings indicate that the MHPP teaching aid is effective in enhancing students’ science process skills and is suitable for renewable energy-based physics learning